PENGIMBASAN PENDIDIKAN BERWAWASAN LINGKUNGAN PADA MAHASISWA PPG PRAJABATAN - Jafar; Wahyudin Madil (PT. CASA CENDEKIA MEDIA, 2025)
Environmentally conscious education is an educational approach that emphasizes understanding and awareness of the natural and social environment. This includes an understanding of environmental problems, efforts to maintain and protect the environment, as well as ways to create sustainability in the environment. Environmental education aims to form individuals who are aware of the importance of protecting and preserving the environment. In the context of formal education, environmentally friendly education can be integrated into the curriculum at all levels, from elementary school to university. Environmentally friendly education can also be implemented informally, such as through environmental activities outside of school or through environmental campaigns involving the community. The main aim of environmentally friendly education is to create a society that is aware of the importance of protecting the environment for human welfare and the survival of life on earth.